COMMERCIAL CREDIT AND COLLECTION PRACTICES OF SELECTED FOOD AND BEVERAGE MANUFACTURING FIRMS IN MAKATI, METRO MANILA - Soewignyo, Tonny (JIU (Jurnal Ilmiah Unklab), 2002)
Offering credit terms has become a competitive tool to entice potential customers however business executives have become worry because of slower economic growth, a worker purchasing power and higher inflation. This study provides some perceptions from the food and beverage manufacturing giving credit and collection practices. The firms service of credit information was customer’s payment history and bank reference. Character and capacity of the management were the highest criteria. All firms preferred cash on delivery, or used o sale force in collection.